IMPROVEMENT OF METHODS FOR DIAGNOSIS AND PREDICTION AT SURGICAL CORRECTION OF NASAL SEPTUM DEVIATION - Shushlyapina, N.O. (World of Medicine and Biology, 2018)
This paper suggests approaches to improving methods for diagnosis and prediction at surgical correction of the nasal septum deviation. A method is introduced to assess the effect of air flow on the nasal cavity walls at micro level. The computer planning method of surgical endonasal plasty is suggested, based on the construction of a volumetric aerodynamic model of the nasal cavity according to the computer tomography and rhinomanometry data. The issues connected with diagnostics and surgical treatment of respiratory-olfactory disorders are considered.
Keywords: nasal septum deviation; surgical endonasal plasty; aerodynamic model of nasal cavity; computer tomography; rhinomanometry